Analysis of the vascular flora in the Cajas National Park (Central Andes, Ecuador) - Ansaloni, Raffaella; Izco, Jesús; Amigo, Javier; Minga, Danilo (Mediterranean Botany, 2022)
The Cajas National Park (CNP) is located 30 km from the city of Cuenca (Ecuador), in the western Andean chain and occupies an area of almost 30,000 ha, between 3300-4450 m of altitude, and includes various ecosystems: subpáramo, herbaceous paramo and super-páramo, which include grasslands (dominant in CNP), wetlands, Polylepis sp. pl. and scrubs; above 4200 m, bush communities adapted to extreme edaphoclimatic conditions dominate. For the elaboration of the catalogue of the vascular flora of the CNP, we compiled, refined and analysed the information available in the herbaria of the University of Azuay (Cuenca, Ecuador) (HA), Missouri Botanical Garden (MO), Pontificia Universidad Católica de Ecuador (QCA) and Tropicos® database, with records of altitudes above 3300 m asl and our collections in the years 2012-2019. 666 species are documented, belonging to 264 genera and 89 botanical families; we describe their biological form (biotype), habitat, distribution ‒with special attention to endemic and non-native species‒ and degree of threat. Finally, the data for each of these criteria are jointly analysed and compared with other Andean mountain ranges. Dichondra macrocalyx Meisn. and Piptochaetium tovarii Sánchez Vega are reported for the first time in Ecuador.